The Challenges Of Vocational Education In Albania - Sela, Ermira (European Scientific Journal, ESJ, 2016)
Education is seen as one of the main instruments for the development of the individual and the economic growth of a country. In particular, vocational education with its practical components is a very important tool in this. One of his objectives is to contribute to the fight against young unemployment by increasing their skills level. Even in Albania, the employment of this category and their qualifications are problems that require solutions. At this point, we stress that VET is the kind of education for which Albania has already need because it represents an important factor to deal with these issues. This work tries to give an overview of the various challenges that VET system in Albania is facing. The method used has been qualitative. The data has been gathered from official sources with reference to enforcement of educational policies.